Kemungkinan Penerapan Konsep Sistem Seting Dalam Penemukenalan Penataan Ruang Kawasan - nfn. Haryadi (Balai Arkeologi Yogyakarta, 1995)
The development of archaeological research activities from the dimensions of form to the dimensions of space requires the support of theories or concepts related to space. One of the activities in the field of archaeology that needs to be supported by the theory or concept of space is the conservation of archaeological resources on an area scale.